A Ku-Band Magnified Active Tx/Rx Multibeam Antenna Based on a Discrete Constrained Lens - Gianfranco Ruggerini (MDPI AG, 2021)
This paper presents the design, manufacturing, and testing of a Ku-band magnified active Tx/Rx multibeam antenna based on a discrete constrained lens. Multibeam antennas based on constrained lenses generate a significant number of beams on a large operative frequency bandwidth. The main novelty and challenge in this development are associated with the combined transmitting and receiving functionality of this active array. An innovative RF building blockchain working in dual-polarization and covering both the transmitting and receiving bandwidth is successfully implemented. In order to improve the accommodation constraints and the thermal control, the active lens is magnified by two confocal paraboloidal reflectors. To validate the design procedure, experimental results are compared with numerical ones.